Useful public health countermeasures to control the current multicountry outbreak of Monkeypox disease - Diatta, Khadija Leila El Siby; Faye, Oumar; Sall, Amadou Alpha; Faye, Ousmane; Faye, Martin (Frontiers in Public Health, 2023)
Monkeypox is a viral disease endemic to some countries in Central and Western Africa. However, sporadic human cases have also been reported outside of Africa. The first human case was reported in 1970 in the Democratic Republic of Congo. Very similar to the eradicated smallpox regarding its clinical representation, the Monkeypox disease is most common in children aged between 5 and 9 years with a fatality rate ranging from 1 to 11% in Africa. During the past decade, the number of countries that reported human cases of the disease grew significantly, while experts still sought knowledge on the characteristics of the virus. The recent increase in Monkeypox cases in many countries raises the concern about a possible global health threat. There is a need to subsequently provide insights into the incidence of Monkeypox disease and come up with mechanisms to prevent its emergence and contain its spread. Furthermore, it is crucial to have a better view of the global diagnostic capacity of the Monkeypox virus. This review aims to assess useful public health countermeasures to control the current multicountry outbreak of Monkeypox disease. Articles were searched in PubMed and Google Scholar electronic databases on 30 June 2022, using selected keywords, without language and date restriction. A total of 44 scientific records were published between 1 January 1962 and 30 June 2022. Herein, we discuss the epidemiological and public health situation at a global scale, provide an updated overview and data of utility for a better understanding of knowledge and research gaps in the epidemiology of the Monkeypox disease, and give useful measures for controlling the current multicountry outbreak.